Occupational Diseases and Perceived Health in Operating Room Nurses: A Multicenter Cross-Sectional Observational Study - María del Mar Martí-Ejarque RN, MSc, MEd; Gemma Guiu Lázaro RN; Roser Coutado Juncal RN; Salvador Pérez Paredes RN; Cecilia Díez-García RN, MSc (SAGE Publishing, 2021)
Background The surgical environment has multiple factors that could affect nurses' health. The aim was to determine the effects of the working environment of operating room nurses on their health compared to hospitalization nurses. Methods A sample of operating room nurses and hospitalization nurses were included in the study and participated by filling in a self-report survey containing sociodemographic data items, the validated Nordic and SF12 scales and a list of medical conditions. Results Three hundred and thirty-one nurses participated in the study. Statistically significant results had obtained for diagnoses of musculoskeletal disorders and contact dermatitis among the operating room nurses. Conclusion/Application to Practice Continuous training in ergonomics is essential. Moreover, surgical protocols for preventing infection should be revised, optimizing the chlorhexidine content of soaps to reduce the risk of lesions among the surgical staff.